A case of coronary microfistula: A newborn microfistula - Cerit, Levent (Indian Heart J, 2016)
Coronary artery fistula is an abnormal connection between a coronary artery and a cardiac chamber, a great artery or the vena cava. Although coronary artery fistulas are known to be congenital malformations they might occur due to infection, trauma or may be iatrogenic. We present a case with acquired coronary microfistula, without any history of interventional procedure.